A Reliable Tool Based on the Fuzzy Logic Control Method Applying to the DC/DC Boost Converter of Off-Grid Photovoltaic to Track the Maximum Power Point - Thanh, Pham Hong; Dai, Le Van (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Solar energy performs an important role in electric energy based on renewable energy generation systems when referring to clear energy. Systems for harvesting renewable energy frequently use DC/DC converters, especially solar photovoltaic systems. The DC/DC boost converter has been used for converting the output voltage from the solar PV system to the required voltage rating of the utility grid under the disturbance in the photovoltaic temperature and irradiation level. Because of that, a new maximum power point tracking based on the fuzzy logic controller (MPPT-FLC) algorithm applying the DC/DC boost converter is developed. The proposed approach aims toward improving the PV system’s performance and tracking effectiveness. This aim can be achieved by adjusting the DC/DC boost converter’s duty cycle to ensure that the PV system operates close to its MPP under varying environmental conditions. The effectiveness of the proposed method is verified in the off-grid PV system under conditions of the change of irradiation and temperature, and the comparison of between the proposed method, the incremental conductance (INC), perturb and observe (P&O), and modified P&O methods is also made. The obtained simulation results show that the MPPT capability significantly improved and achieved the highest MPPT efficiency of 99.999% and an average efficiency of 99.98% in total when applying the proposed method.